Black Scale Saissetia oleae (Olivier, 1791) (Insecta: Hemiptera: Coccoidea: Coccidae) - Morgan A. Byron; Jennifer L. Gillett-Kaufman; Sandra A. Allan (EDIS, 2015)
The black scale is an important pest of citrus and olive trees. Originally from South Africa, this scale is now distributed worldwide. In Florida, black scale is found on citrus, cultivated olive, avocado, and many popular landscape plants. It is likely that black scale, like many invasive pests, was imported to the United States on infested nursery plants. Based on their small size and the unique life history of scale insects, these insects are difficult to detect and control. This 4-page fact sheet was written by Morgan A. Byron, Jennifer L. Gillett-Kaufman, and Sandra A. Allan, and published by the UF Department of Entomology and Nematology, March 2015. (Photo credit: Lyle Buss, UF/IFAS)